Cost-utility and cost-benefit analyses of school-based obesity prevention program - Haiquan Xu; Yanping Li; Songming Du; Qian Zhang; Ailing Liu; Junmao Sun; Guansheng Ma (BMC, 2020)
Abstract Background Economic evaluation of school-based obesity interventions could provide support for public health decision of obesity prevention. This study is to perform cost-utility and cost-benefit assessment of three school-based childhood obesity interventions including nutrition education intervention (NE), physical activity intervention (PA) and comprehensive intervention (both NE and PA, CNP) with secondary data analysis of one randomized controlled trial. Methods The standard cost-effectiveness analysis methods were employed from a societal perspective to the health outcome and costs that are attributable to the intervention. NE, PA and CNP were carried out separately for 2 semesters for childhood obesity interventions in primary schools. The additional quality-adjusted life years (QALYs) resulting from the interventions were measured as the health outcome. A cost-utility ratio (CUR) and A cost-benefit ratio (CBR) was calculated as the ratio of implementation costs to the total medical and productivity loss costs averted by the interventions. Results The CUR and CBR were ¥11,505.9 ($1646.0) per QALY and ¥1.2 benefit per ¥1 cost respectively, and the net saving was ¥73,659.6 ($10,537.9). The CUR and CBR for nutrition education and physical activity interventions were ¥21,316.4 ($3049.6) per QALY and ¥0.7 benefit per ¥1 cost, ¥28,417.1 ($4065.4) per QALY and ¥0.4 benefit per ¥1 cost, respectively (in 2019 RMB). Compared with PA intervention, the ICERs were ¥10,335.2 ($1478.6) and 4626.3 ($661.8) for CNP and NE respectively. The CBR was ¥1.2, 0.7, and 0.4 benefits per ¥1 cost for CNP, NE, and PA interventions, respectively. Net estimated savings were achieved only through CNP intervention, amounting to ¥73,659.6 ($10,537.9). Conclusions Comprehensive school-based obesity intervention is a beneficial investment that is both cost-effective and cost saving. Compared with PA intervention, both CNP and NE intervention were more cost-effective.